ATTENTION AND INTERNATIONAL HIV DEMENTIA SCALE (IHDS) DO NOT CORRELATE WITH CD4 COUNT IN HIV PATIENTS - Arofah, Annisa Nurul; Rianawati, Sri Budhi; Rasyid, Harun Al; Rahayu, Masruroh (Malang Neurology Journal, 2018)
Background. Despite it is common neurocognitive domain that affected in patient with Human Immunodeficiency Virus (HIV) infection, attention domain is not assessed using International HIV Dementia Scale (IHDS), a common screening test to diagnose HIV-associated cognitive disorder. Detection of attention deficit in HIV patient is important as it can maintain the capacity to adherence to antiretroviral therapy and essential to activity daily living. CD4 is one of the markers for severity of HIV infection. Objective. We aims to correlate between CD4 with IHDS and CD4 with attention performance test, such as forward digit span test (FWD), backward digit span test (BWD), and trail making test A test (TMA).Methods. This is an analytic study using cross sectional design. 20 respondents are collected for the study using purposive sampling. Data is collected using instrument IHDS, FWD, BWD, and TMA.Results. Using the correlation of Eta, Eta 2 of CD4 and IHDS, CD4 and FWD, CD4 and BWD, also CD4 and TMA are 0.025, 0.022, 0.022 and 0.011.Conclusion. We concluded that CD4 have no correlation with test for attention domain and IHDS.